Indoor Black Carbon Concentrations and their Sources in Residential Environments: Validation of an Input-adaptive Proxy Model - Jiangyue Zhao; Pak Lun Fung; Martha Arbayani Zaidan; Birgit Wehner; Kay Weinhold; Alfred Wiedensohler; Tareq Hussein (Aerosol and Air Quality Research)
Abstract Exposure to black carbon (BC) in the residential environment was found to be positively associated with elevated blood pressure and cardiovascular disease. However, BC has been under-measured and under-studied compared to other common indoor gaseous and particulate pollutants. Representative indoor mass concentrations of equivalent black carbon (eBC) and the sources’ contribution from indoors and outdoors in real-life residential environments in 40 German households were evaluated and presented in this work. During the 500 measurement days, the mean indoor eBC mass concentration was 0.6 µg m−3, which is less than half of the outdoor concentration in the urban background in Germany. However, common indoor sources contributed differently to indoor eBC, which also resulted in higher mass concentrations in the cold season than in the warm season. Indoor pollutant measurements are often performed with only a limited number of instruments and pollutant data. To fill in the missing knowledge of indoor BC, a proxy model was developed. This proxy model can predict indoor eBC concentrations based on existing indoor databases or in cases where direct measurements of indoor eBC concentrations are not available. Due to the complex influence of climate and indoor activities, the model separated six scenarios for weather (including warm and cold seasons) and indoor activities (burning, non-burning, and other activities) for typical urban residential environments in Germany. In this study, indoor eBC mass concentrations were found to be best estimated by indoor and outdoor PM1. For different scenarios, the model achieved a satisfactory to good coefficient of determination (0.49 < R 2 < 0.77). With the aid of this model, a more accurate prediction of indoor eBC mass concentration and the resulting exposure and health risk assessment can be achieved for households under similar climatic conditions and activity habits of the occupants, e.g., in Central Europe.